2017
DOI: 10.2147/ott.s127202
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of DcR3 sensitizes hepatocellular carcinoma cells to TRAIL-induced apoptosis

Abstract: Decoy receptor 3 (DcR3) has been recently described as an antiapoptosis and prometastasis factor since it can competitively bind to FasL, TL1A, and LIGHT, and it is highly expressed in many malignant tumors. Downregulation of DcR3 can promote tumor cell apoptosis and inhibit metastasis. A previous study demonstrated that reduction of DcR3 could induce tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-mediated apoptosis in pancreatic cancer cells. However, whether such an effect is seen in hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…[ 38 39 40 ] Some studies confirmed that many tumor cells are resistant to TRAIL, including HCC cells. [ 41 42 ] It has previously been shown that activation of the PI3K/Akt pathway promotes tumor cell tolerance to TRAIL, whereas inhibition of this pathway can make tumor cells susceptible to TRAIL. [ 20 ] Because reduction of XB130 can inhibit the activation of PI3K/Akt, we explored whether XB130 contributes to the resistance to TRAIL by HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 39 40 ] Some studies confirmed that many tumor cells are resistant to TRAIL, including HCC cells. [ 41 42 ] It has previously been shown that activation of the PI3K/Akt pathway promotes tumor cell tolerance to TRAIL, whereas inhibition of this pathway can make tumor cells susceptible to TRAIL. [ 20 ] Because reduction of XB130 can inhibit the activation of PI3K/Akt, we explored whether XB130 contributes to the resistance to TRAIL by HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In TNF superfamily, the cytokine of TNF-related apoptosis-inducing ligand (TRAIL) is considered as a potential anti-tumor agent. Treatment with TRAIL effectively kills multiple cancer cells, such as hepatocellular carcinoma cells and colorectal cancer [ 11 , 12 ]. As TRAIL induces significant apoptosis selectively in tumor cells without influencing the function of normal cells, it has been tested in clinical trials for treatment of various cancers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decoy receptor 3 (DcR3 or TNFRSF6B) is a soluble receptor belonging to the tumor necrosis factor receptor superfamily (TNFRSF) that binds competitively to other TNFSF members, such as Fas ligand (FasL/TNFSF6/ CD95L), 4 LIGHT (TNFSF14), 5 and TNF-like molecule 1A (TL1A/TNFSF15). 6 Upregulation of DcR3 was associated with poor prognosis in several malignancies [7][8][9][10][11][12][13][14][15][16] due to its effect on angiogenesis and the proliferation, invasion, and metastasis of tumor cells. [7][8][9][17][18][19] However, very few studies have explored the clinicopathological role of DcR3 in oral cancer.…”
Section: Introductionmentioning
confidence: 99%